Answer:
13 seconds.
Step-by-step explanation:
Given
[tex]h = -4.9(t - 13)(t + 2).[/tex]
Required
Determine a reasonable solution for t
To do this, we equate h to 0.
[tex]h = -4.9(t - 13)(t + 2).[/tex] becomes
[tex]0 = -4.9(t - 13)(t + 2).[/tex]
Divide through by -4.9
[tex]0 = (t - 13)(t + 2).[/tex]
Reorder the expression
[tex](t - 13)(t + 2) = 0.[/tex]
Split
[tex]t-13 = 0[/tex] or [tex]t + 2 = 0[/tex]
This gives:
[tex]t = 13[/tex] or [tex]t = -2[/tex]
But time can't be negative, So:
[tex]t = 13[/tex]